2000
DOI: 10.1161/01.atv.20.11.2394
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1 Receptor Antagonist Expression in Human Endothelial Cells and Atherosclerosis

Abstract: Abstract-The proinflammatory cytokine interleukin (IL)-1 is expressed mainly within the endothelium of atherosclerotic plaques and may be linked with inflammatory mechanisms of atherogenesis. IL-1 action is complex and regulated in part by its naturally occurring inhibitor, the IL-1 receptor antagonist (IL-1ra). Therefore, we studied differential and specific isoform expression of IL-1ra in the endothelium of diseased coronary arteries and in endothelial cells (ECs) stimulated under defined conditions. In view… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
136
0
11

Year Published

2002
2002
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(153 citation statements)
references
References 33 publications
6
136
0
11
Order By: Relevance
“…6 IL-1ra may also derive from the vessel wall itself. 7 It is recognized that significant local cellular or tissue generation of cytokines can occur without a corresponding increase in circulating levels, but the cytokine measurements in this study confirm that a systemic response was generated, with a profile similar to that reported previously. 3 The lack of effect on CRP is expected because of the relatively short time course of this study.…”
Section: Aspirin Pretreatment Preserves Endothelial Functionsupporting
confidence: 87%
“…6 IL-1ra may also derive from the vessel wall itself. 7 It is recognized that significant local cellular or tissue generation of cytokines can occur without a corresponding increase in circulating levels, but the cytokine measurements in this study confirm that a systemic response was generated, with a profile similar to that reported previously. 3 The lack of effect on CRP is expected because of the relatively short time course of this study.…”
Section: Aspirin Pretreatment Preserves Endothelial Functionsupporting
confidence: 87%
“…In columnar epithelial cells, IL-1RN*2 has been shown to be associated with reduced protein content (69). In Dewberry et al (65), the association of IL-1RN*2 with decreased icIL-1ra protein production in HUVECs was also documented. Association of IL-1RN*2 with DCM could be one possible explanation of reduced IL-1ra gene expression in DCM myocardium.…”
Section: Discussionmentioning
confidence: 93%
“…The alteration of the IL-1/IL-1ra balance has been proposed to be one of the mechanisms promoting progression of cardiovascular diseases. It has been described that coronary arteries of ICM patients expressed more IL-1ra mRNA and immunoreactive IL-1ra protein than DCM arteries (65). In heart tissues, higher expression of IL-1β mRNA was detected in DCM compared with ICM patients, and it may be assumed that the IL-1/IL-1ra balance could be disturbed by this enhanced IL-1 production (14).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported that a genetic variant of IL-1ra is linked with reduced icIL-1ra1 production by EC [8] and a diminished proliferative capacity by EC [9]. Other studies have suggested a role for G1 cell cycle proteins in the IL-1 mediated proliferation of vascular smooth muscle cells [10] and the senescence of ECs [11].…”
Section: Introductionmentioning
confidence: 96%